The Bind of Unilateral Power Dynamics and Youth Voice in School Politics. Issue 1 (January 2022) - Domínguez, Ashley D.; Clement, Valencia; Bertrand, Melanie
Research has shown the value of including youth, especially minoritized students, in school- and district-level educational decision-making. However, power dynamics, as related to adultism, along with other inequities, are barriers to youth's political influence. We elucidate these barriers by exploring the possible relationship between adult-adult power dynamics, on one hand, and levels of student voice in schools, on the other. Interviews with teachers and administrators about youth voice initiatives indicated that bounded rationality illuminates how limiting access to knowledge, a form of power, can impact educator decision-making. In addition, bounded rationality bolsters unilateral power structures and therefore curtails youth voice. However, we also found that building relational power between teachers and students and maneuvering beyond bounded rationality increases opportunities for youth voice.